1991
DOI: 10.1093/oxfordjournals.jbchem.a123700
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Substrate Specificity of Neutral α-Mannosidase Purified from Japanese Quail Oviduct by Using Sugar Chains from Glycoproteins1

Abstract: The substrate specificity of neutral alpha-mannosidase purified from Japanese quail oviduct [Oku, H., Hase, S., & Ikenaka, T. (1991) J. Biochem. 110, 29-34] was analyzed by using 21 oligomannose-type sugar chains. The enzyme activated with Co2+ hydrolyzed the Man alpha 1-3 and Man alpha 1-6 bonds from the non-reducing termini of Man alpha 1-6(Man alpha 1-3)Man alpha 1-6(Man alpha 1-3)Man beta 1-4GlcNAc beta 1-4GlcNAc (M5A), but hardly hydrolyzed the Man alpha 1-2 bonds of Man9GlcNAc2. The hydrolysis rate decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…8), the interaction of free OS with the lysosomal transporter bears similarities to the interactions between free OS and cytosolic glycosidases. Accordingly, the cytosolic chitobiase (15) by definition interacts with the reducing di-N-acetylchitobiose moiety of free OS, but more surprisingly, the cytosolic mannosidase has been found to act only on free OS bearing a single GlcNAc residue at their reducing termini (20). Therefore, these two enzymes and the cytosol-to-lysosome free OS transporter interact with free OS in a manner that involves surveillance of the reducing terminus of the oligosaccharide.…”
Section: The Lysosomal Free Os Transporter Displays a Unique Specificmentioning
confidence: 99%
“…8), the interaction of free OS with the lysosomal transporter bears similarities to the interactions between free OS and cytosolic glycosidases. Accordingly, the cytosolic chitobiase (15) by definition interacts with the reducing di-N-acetylchitobiose moiety of free OS, but more surprisingly, the cytosolic mannosidase has been found to act only on free OS bearing a single GlcNAc residue at their reducing termini (20). Therefore, these two enzymes and the cytosol-to-lysosome free OS transporter interact with free OS in a manner that involves surveillance of the reducing terminus of the oligosaccharide.…”
Section: The Lysosomal Free Os Transporter Displays a Unique Specificmentioning
confidence: 99%
“…These properties were very similar to those of cytosolic -mannosidases found in several animal cells. [21][22][23][24][25] From this circumstantial evidence, we surmised that this cobalt-sensitivemannosidase might be involved in the degradation of high-mannose type N-glycans occurring in developing seeds, although the subcellular localization of thismannosidase in developing seeds remains obscure. Concerning the structural features of high-mannose type free N-glycans (Man9-5GlcNAc1) in plant cells, we have reported that such free N-glycans possess a common structural unit, Man1-6(Man1-3)Man1-6(Man1-3)Man1-4GlcNAc.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26] Interestingly, it has been reported that these cytosolic -mannosidases in animal cells require cobalt ions for optimum activity and that the substrate specificity is regulated by cobalt cation. 26) Since Ginkgo -mannosidase possesses similar enzymatic properties to those of animal cytosolic -mannosidases, we assumed that the -mannosidase might be involved in the turnover of free N-glycans occurring in developing Ginkgo seeds, 7) instead of the turnover of aged or denatured glycoproteins in vacuole.…”
mentioning
confidence: 99%
“…[22][23][24] In previous studies, 25,26) however, we purified an -mannosidase from Ginkgo seeds that was activated by cobalt ion and preferred highmannose type glycans with one GlcNAc residue rather than those with the chitobiosyl unit. Since these enzymatic properties are very similar to those of animal cytosolic -mannosidase [22][23][24] that has been thought to be involved in the degradation of high-mannose type free N-glycans produced by PNGase and ENGase in animal cells, [19][20][21][22] Ginkgo -mannosidase might be responsible for the degradation of high-mannose type free N-glycans in the cytosol. Furthermore, this speculation is supported by another fact that the Ginkgo enzyme converted Man 9 GlcNAcNAc 1 to a Man 5 GlcNAc 1 isomer, Man 1-6(Man 1-3)Man 1-6(Man 1-3)Man 1-4GlcNAc, found specifically in plant cells but not to the Man 1-6(Man 1-2Man 1-2Man 1-3)Man 1-4GlcNAc structure found in animal cells.…”
Section: Discussionmentioning
confidence: 99%